2015
DOI: 10.3109/09638288.2015.1019011
|View full text |Cite
|
Sign up to set email alerts
|

Promoting physical activity in rheumatoid arthritis: a narrative review of behaviour change theories

Abstract: To date, behaviour change interventions conducted in RA populations to increase physical activity levels have not had a strong theoretical underpinning. It is proposed that an intervention utilising the theory of planned behaviour is developed with the aim of increasing physical activity in people with RA. Implications for Rehabilitation Interventions to promote physical activity in the rheumatoid arthritis (RA) population have failed to change participants' behaviour. A small number of studies have used behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…More importantly, the behaviour change techniques appeared to be selected ad hoc for the majority of interventions, with no due consideration to the importance of the use of behaviour change theory when designing and delivering interventions which seek to change behaviour, in this case physical activity. A recent review [46] has highlighted this issue in interventions targeting physical activity behaviour in the RA population and is an important consideration for future research.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the behaviour change techniques appeared to be selected ad hoc for the majority of interventions, with no due consideration to the importance of the use of behaviour change theory when designing and delivering interventions which seek to change behaviour, in this case physical activity. A recent review [46] has highlighted this issue in interventions targeting physical activity behaviour in the RA population and is an important consideration for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have found that expectancy-value models, such as the Theory of Planned Behavior (TPB: Ajzen, 1985), predict intention well (McEachan et al, 2011), there is still a large proportion in behavior left unexplained (Armitage and Conner, 2001). Unfortunately, the use of correlational data, which insufficiently validates a theory (Weinstein, 2007), far outweighs the number of studies attempting to change these processes through the development of interventions (Hardeman et al, 2002). This is despite the prevalence of clear methodological guidelines on belief alteration (Ajzen, 1991).…”
Section: Conscious Processes In Behavior Changementioning
confidence: 99%
“…It was evident that the interventions conducted to date had not involved key stakeholders when seeking to design the behaviour change intervention (20)(21). The MRC (14) advocates the involvement of key stakeholders when designing complex interventions and so to compliment the quantitative reviews in stage 1 of the MRC qualitative interviews with people who have RA and HPs who work in rheumatology were conducted.…”
Section: Behaviour Change Wheel Step 4: Identify What Needs To Changementioning
confidence: 99%
“…A sound theoretical underpinning is essential in complex interventions in understanding how the intervention causes change, so that weak links in the causal chain can be identified and strengthened (14). To date interventions which have targeted physical activity behaviour change in people who have RA have lacked this theoretical understanding (20)(21). This poses a challenge when seeking to improve upon the design of previous interventions which targeted physical activity behaviour, as the effective components and how change came about within an intervention cannot be identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation